A LAIR1 insertion generates broadly reactive antibodies against malaria variant antigens - Tan, Joshua; Pieper, Kathrin; Piccoli, Luca; Abdi, Abdirahman; Foglierini, Mathilde; Geiger, Roger; Maria Tully, Claire; Jarrossay, David; Maina Ndungu, Francis; Wambua, Juliana; Bejon, Philip; Silacci Fregni, Chiara; et al. (Nature (London), 2016)
Monoclonal antibodies with broad reactivity against antigens on the parasite that causes malaria, Plasmodium falciparum , are isolated from two subjects and are found to have an unusual insertion of an immunoglobulin-like domain from a different chromosome, illustrating a new mechanism of antibody diversification. Broadly reactive anti-malarial antibodies This paper reports the isolation of monoclonal antibodies with broad reactivity against Plasmodium falciparum antigens from two subjects living in a malaria-endemic region in Kilifi, Kenya. The antibodies are unusual in that they carry large insertions of an immunoglobulin-like domain from LAIR1, an Ig superfamily inhibitory receptor encoded on chromosome 19. The antibodies bind to polymorphic surface antigens on the parasite surface; binding depends on the mutated form of the insert. These findings illustrate a novel mechanism of antibody diversification, and the existence of conserved epitopes that may be suitable candidates for the development of a malaria vaccine. Plasmodium falciparum antigens expressed on the surface of infected erythrocytes are important targets of naturally acquired immunity against malaria, but their high number and variability provide the pathogen with a powerful means of escape from host antibodies 1 , 2 , 3 , 4 . Although broadly reactive antibodies against these antigens could be useful as therapeutics and in vaccine design, their identification has proven elusive. Here we report the isolation of human monoclonal antibodies that recognize erythrocytes infected by different P. falciparum isolates and opsonize these cells by binding to members of the RIFIN family. These antibodies acquired broad reactivity through a novel mechanism of insertion of a large DNA fragment between the V and DJ segments. The insert, which is both necessary and sufficient for binding to RIFINs, encodes the entire 98 amino acid collagen-binding domain of LAIR1, an immunoglobulin superfamily inhibitory receptor encoded on chromosome 19. In each of the two donors studied, the antibodies are produced by a single expanded B-cell clone and carry distinct somatic mutations in the LAIR1 domain that abolish binding to collagen and increase binding to infected erythrocytes. These findings illustrate, with a biologically relevant example, a novel mechanism of antibody diversification by interchromosomal DNA transposition and demonstrate the existence of conserved epitopes that may be suitable candidates for the development of a malaria vaccine.